1982
DOI: 10.1128/aac.22.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-alkynoic acids on in vitro growth of bacterial and mammalian cells

Abstract: 3-Decynoyl-N-acetylcystamine is known to inhibit the in vitro growth of Escherichia coli but not of yeasts or mammalian cells. Neither the free acid nor the 2 positional isomer is active (L. R. Kass, J. Biol. Chem. 243:3223-3228, 1968). Other studies have shown that 2-hexadecynoic acid is fungitoxic whereas most of the shorter chain isomers are inactive (H. Gershon and L. Shanks, Can J. Microbiol. 24:591-597, 1978). Since these studies suggested that positional or chain length isomers of the acetylenic acids m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…In addition, it was previously reported that despite the fact that 2-hexadecynoic acid inhibits the growth of HeLa cells, the simultaneous addition of palmitic acid to the culture medium reverses the growth inhibition observed in HeLa cells, thus implying that toxicity would not occur in animals consuming a normal diet (3).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, it was previously reported that despite the fact that 2-hexadecynoic acid inhibits the growth of HeLa cells, the simultaneous addition of palmitic acid to the culture medium reverses the growth inhibition observed in HeLa cells, thus implying that toxicity would not occur in animals consuming a normal diet (3).…”
Section: Resultsmentioning
confidence: 97%
“…The optimal chain lengths (between 8 and 16 carbons) have been established for the 2-alkynoic FA to exert maximum fungistatic effects (2). Among the 2-alkynoic FA 2-hexadecynoic acid has received the most attention for its antifungal, antimicrobial, and cytotoxic properties (3)(4)(5). The bioactivity of 2-hexadecynoic acid has been ascribed to its ability to inhibit the elongation of saturated and unsaturated FA as well as its potential to inhibit the FA acylation process, particularly triglyceride synthesis (4)(5).…”
mentioning
confidence: 99%
“…A recent comprehensive review on acetylenic lipids, which also covered acetylenic acids, highlighted their anticancer activities (12). The antibacterial, anti-human immunodeficiency virus, and pesticidal activities of some acetylenic acids have also been reported (5,9,13,17,18,22). Several studies have also shown that natural and synthetic acetylenic acids have activity against human and agricultural fungal pathogens (5,9,14,16,17,24).…”
Section: Vol 52 2008 Antifungal Activities Of Acetylenic Acids 2445mentioning
confidence: 97%
“…Several studies have also shown that natural and synthetic acetylenic acids have activity against human and agricultural fungal pathogens (5,9,14,16,17,24). As with the antibacterial activity, their antifungal activity is generally associated with their chain length and positional triple bond (6,16,22,28). For example, 4-, 5-, and 6-octynoic acids and 9-undecynoic acid are antifungal against T. mentagrophytes, with the last being the most active compound and slightly less potent than undecylenic acid (9).…”
Section: Vol 52 2008 Antifungal Activities Of Acetylenic Acids 2445mentioning
confidence: 99%
“…2-AFAs are acetylenic fatty acids which have the peculiarity of containing a triple bond (C≡C) at C-2 in their structures. Acetylenic fatty acids have been widely studied by medicinal chemists due to their interesting antimicrobial properties such as antifungal (Carballeira, 2008; Carballeira et al, 2006; Carballeira et al, 2005; Gershon and Shanks, 1978; Li et al, 2003; Li et al, 2008; Xu et al, 2012), antiprotozoal (Carballeira et al, 2012; Tasdemir et al, 2010), and antibacterial activities (Konthikamee et al, 1982; Morbidoni et al, 2006). Acetylenic fatty acids are mainly produced by certain plants as a chemical defense against microorganisms (Cahoon et al, 2003; Carballeira, 2008; Fatope et al, 2000; Li et al, 2003; Li et al, 2008; Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%